FinTech sebagai Katalisator Inovasi Produk Keuangan Syariah: Peluang dan Tantangan - Nur Fadlan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Fintech has significantly transformed the landscape of the Islamic financial industry and is widely recognized as a key catalyst for innovation in Islamic financial products. The advancement of digital technology enables the integration of Sharia principles with modern financial systems that are more inclusive, efficient, and responsive to societal needs. This study aims to analyze the role of fintech in driving innovation in Islamic financial products and its contribution to enhancing Islamic financial inclusion. The research adopts a descriptive qualitative methodology using a literature review approach by examining academic articles, books, industry reports, and relevant regulations related to Islamic fintech. The findings indicate that the characteristics of fintech within the Islamic finance context are generally aligned with Sharia compliance, particularly in terms of transparency, fairness, and the avoidance of riba, gharar, and maysir. Furthermore, fintech serves as a strategic solution for expanding Islamic financial inclusion, especially among unbanked communities and micro, small, and medium enterprises (MSMEs). Fintech-driven innovations include improved access to financial services, greater product diversification, cost efficiency, enhanced transaction transparency, and personalized financial services.